Reactualization of Student-Oriented Educational Evaluation: A Pedagogical Perspective in Junior High School: A Mini Research Exploring Student-Oriented Educational Evaluation Practices at SMP Negeri 2 Dawuan - Gina Meilina Syarifah; Muhamad Parhan (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to explore the practices of student-centered educational evaluation at State Junior High School 2 Dawuan. Educational evaluation is a crucial component of the learning process that not only measures final outcomes but also supports the comprehensive development of students' skills and understanding. Using a qualitative approach and case study design, data were collected through questionnaires from 20 teachers to understand their perspectives on evaluations that are responsive to students' needs. The research findings reveal that although most teachers recognize the importance of student-centered evaluation, its implementation in the field still faces various challenges. Approximately 50% of teachers report using diverse evaluation instruments, but only around 30% consistently apply diagnostic assessments. These findings indicate a gap between theory and practice in the implementation of educational evaluation at this junior high school. The study recommends the need for further teacher training and the development of educational policies that support the implementation of student-centered evaluation methods to improve learning quality.